Volunteering in adaptive sport: effects of altruistic and egoistic motivation on performance and sustained intention - Han, Keunsu; Kim, Kyoung Tae (Frontiers in Sports and Active Living, 2025)
IntroductionAdaptive sport events provide a unique volunteer setting emphasizing inclusion, accessibility, and individualized support for athletes with disabilities. Volunteers are essential not only to event operations but also to fostering a positive and empowering experience for athletes. Despite extensive research on sport volunteerism, studies focusing specifically on the adaptive sport context remain limited. This study explores how altruistic and egoistic motivations influence volunteers' in-role performance and their sustained intention in adaptive sport settings.MethodsA self-reported questionnaire was administered to volunteers at the 2024 Korean-American Adaptive Sport Festival in Maryland, USA, using a convenience sampling method. A total of 212 valid responses were included in the analysis. To address the study's objectives, data were analyzed using frequency and descriptive statistics, correlation analysis, exploratory factor analysis (EFA), reliability testing, and multiple regression analysis.ResultsThe results indicate that Organization Attachment (OA), Volunteer Attachment (VA), and Internal Benefits (IB) had a positive effect on volunteers' in-role performance, while External Benefits (EB) showed no significant impact. Furthermore, VA and IB had a significant impact on volunteers' sustained intention to continue participating, whereas OA and EB showed no significant effect.DiscussionThese findings offer valuable insights into volunteer motivation and its impact on in-role performance and continued engagement in adaptive sport settings. The study offers practical implications for building a more committed, capable, and sustainable volunteer workforce to support the continued success of adaptive sport programs.